Silent night: retrospective database study assessing possibility of "weekend effect" in palliative care. (16th December 2014) - Voltz, Raymond; Kamps, Robert; Greinwald, Ralf; Hellmich, Martin; Hamacher, Stefanie; Becker, Gerhild; Kuhr, Kathrin; Gaertner, Jan
Abstract : Objective To compare the mortality of patients in a palliative care unit on working days with that on weekends and public holidays. Design Retrospective database study. Setting Palliative care unit in Germany. Population All admissions to palliative care unit between 1 January 1997 and 31 December 2008. Main outcome measure The impact of day type (working days or weekends and public holidays) on mortality was analysed using Poisson regression models. Results A total of 2565 admitted patients and 1325 deaths were recorded. Of the deaths, 448 (33.8%) occurred on weekends and public holidays. The mortality rate on weekends and public holidays was 18% higher than that on working days (mortality rate ratio 1.18, 95% confidence interval 1.05 to 1.32; P=0.005). Conclusion Patients in the palliative care unit were at higher risk of dying on weekends and public holidays. In the absence of a prospective study, the exact reasons for this correlation are unclear.